PENGGUNAAN PROGESTERON DAN ESTRADIOL BENZOAT PADA PROGRAM INSEMINASI BUAT AN DOMBA ST. CROIX The Effects of Progesterone and EstradiPl enzoate of AI in the St. Croix ewes. - Feradis Feradis (State Islamic University of Sultan Syarif Kasim Riau, 2006)
The objectives of this research are to determinetli effects of progesterone intravaginal implant and its . combination with estradiol benzoate on response of estrus d ;conception rate.Results of the experiment. indicated that both treatnien of progesterone alone and progesterone plus estradiolbenzoate induced estrus in all treated ewes. The onset of was earlier in the group treated with 0.1 fig estradiolbenzoate than in the group treated with progesterone alone'(S2.31 and 42.31 hours respectively, after progesteroneimplant removal). The duration of estrus was longer in gr ptreated with 0.1 mg estradiol benzoate (70.92 hours)than in the group treated with progesterone alone (37.42 hoUrs). The conception rate after insemination in the grouptreated with progesterone alone was not different with the gr#p treated with progesterone and estradiol benzoate:It is concluded that administration of estradiol benzoatE after progesterone implant removal improves estrousresponse, but can not improve the conception rate compared With progesterone treatment alone.